A mixed-integer quadratically-constrained programming model for the distribution system expansion planning - Franco, John F.; Rider, Marcos J.; Romero, Rubén (International journal of electrical power & energy systems, 2014)
•A model to obtain the steady-state operation of a distribution system is shown.•A quadratically-constrained model for the distribution system planning is proposed.•We reported better results for test cases than the ones presented in other works. This paper presents a mixed-integer quadratically-constrained programming (MIQCP) model to solve the distribution system expansion planning (DSEP) problem. The DSEP model considers the construction/reinforcement of substations, the construction/reconductoring of circuits, the allocation of fixed capacitors banks and the radial topology modification. As the DSEP problem is a very complex mixed-integer non-linear programming problem, it is convenient to reformulate it like a MIQCP problem; it is demonstrated that the proposed formulation represents the steady-state operation of a radial distribution system. The proposed MIQCP model is a convex formulation, which allows to find the optimal solution using optimization solvers. Test systems of 23 and 54 nodes and one real distribution system of 136 nodes were used to show the efficiency of the proposed model in comparison with other DSEP models available in the specialized literature.